Tunnel waste slag unfired water permeable brick and preparation method thereof
By combining tunnel slag discard with other raw materials and using press molding method to prepare burn-free water-free bricks, the problem of tunnel slag accumulation is solved and the performance and resource utilization of building materials are improved.
Patent Information
- Application Number
- CN202510090282.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-21
- Publication Date
- 2025-04-15
AI Technical Summary
The accumulation of waste slag generated during tunnel construction causes environmental pollution and waste of resources. It is difficult for the existing technology to effectively use these waste slag to prepare high-performance building materials.
Tunnel waste slag is used as aggregate, combined with raw materials such as microsilicon powder, iron tailings, fly ash, silicate cement and pore-forming agents, and burn-free water-free bricks are prepared through press molding to optimize the raw material formula and preparation process.
The mechanical strength and permeability of permeable bricks are improved, effective utilization of tunnel slag is achieved, and environmental pollution and resource waste are reduced.
Smart Images

Figure BDA0005251307050000103 
Figure BDA0005251307050000104 
Figure BDA0005251307050000111
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of building material preparation, and particularly relates to a tunnel waste slag unfired permeable brick and a preparation method thereof. Background Art
[0002] Unfired permeable bricks are a new type of environmentally friendly building material, mainly made through concrete technology. Its raw materials usually include inorganic non-metallic materials, cement, sand and gravel, etc., combined with organic or inorganic binders, and are made through a molding and curing process without high-temperature firing, so they are called unfired permeable bricks. Unfired permeable bricks have many advantages, such as light weight, high strength, durability and good thermal insulation performance. They are suitable for road paving, landscape paving and slope protection in urban construction. In addition, unfired permeable bricks are also highly permeable, which can effectively promote rainwater infiltration, replenish groundwater, alleviate urban waterlogging problems, and help reduce the heat island effect.
[0003] The production process of unfired permeable bricks is also quite diverse, including fully automatic and semi-automatic production lines. These equipment can achieve efficient and environmentally friendly production processes and meet the needs of different scenarios. For example, the unfired permeable brick equipment developed by Xi'an Yinma Company adopts two-time filling and one-time forming processes, which effectively solves the fading problem of permeable bricks and overcomes the contradiction between permeability and strength, making the bricks have both good permeability and high strength.
[0004] Tunnel slag (TuS) is tunnel rock solid waste generated during tunnel excavation construction. Its main mineral components are shale, siltstone, etc. The accumulation of a large amount of tunnel slag brings great harm to the surrounding environment of the construction. Using these engineering slag to prepare unfired permeable bricks can not only turn waste into treasure, but also improve resource utilization, which is beneficial to local economic development. Summary of the invention
[0005] The object of the present invention is to provide a tunnel waste slag unfired permeable brick and a preparation method thereof.
[0006] A tunnel waste slag unfired water-permeable brick is made of the following raw materials in parts by weight: 30-80 parts of tunnel waste slag, 10-30 parts of filler, 10-30 parts of fly ash, 20-50 parts of cement, 1-3 parts of water reducing agent, 4-8 parts of pore-forming agent and 10-20 parts of water.
[0007] The filler is one or more of microsilica powder, iron tailings, boron titanium magnesium stone, and hydroxy boron magnesium stone.
[0008] Preferably, the filler is a mixture of microsilica powder and iron tailings in a mass ratio of 2:1; or a mixture of boron titanium magnesium stone and hydroxy boron magnesium stone in a mass ratio of 1:1.
[0009] The cement is P.O52.5 ordinary Portland cement.
[0010] The water reducing agent is one or more of calcium lignin sulfonate, sodium lignin sulfonate, and sodium β-naphthalenesulfonate formaldehyde condensate.
[0011] The particle size of the tunnel waste is 4-10 mm.
[0012] The pore-forming agent is a mixture of perlite and polystyrene microspheres in a mass ratio of 1:1; the diameter of the polystyrene microspheres is 30-200 um.
[0013] The method for preparing the tunnel waste slag unfired permeable brick is carried out according to the following steps:
[0014] (1) According to the weight ratio, 30-80 parts of tunnel waste are put into a 4-10 mm square sieve for screening, the screened tunnel waste is put into a container for cleaning and drying, 10-30 parts of filler, 10-30 parts of fly ash, 20-50 parts of cement, 1-3 parts of water reducer, 4-8 parts of pore former, and 10-20 parts of water are added, and after mixing evenly, the mixture is put into a cement mortar mixer and stirred for 3-6 minutes to prepare a slurry;
[0015] (2) placing the stirred slurry into a mold, applying pressure and maintaining the pressure for 30-80 seconds to press it into a green body;
[0016] (3) The green body is naturally dried and then cured.
[0017] The applied pressure in step (2) is 5-15 MPa.
[0018] The curing temperature in step (3) is 20-30° C., the curing humidity is greater than 95%, and the curing time is 20-35 days.
[0019] Beneficial effects of the present invention: The present invention adopts tunnel waste as aggregate, adds appropriate amounts of silicate cement and fly ash, and adopts a pressing molding method to prepare non-fired high-performance permeable bricks. By optimizing the raw material formula and preparation process, the mechanical strength and water permeability of the permeable bricks are improved. The combination of microsilica powder and iron tailings and the combination of boron titanium magnesium and hydroxy boron magnesium in the formula improves the mechanical properties of the material, and the combination of perlite and polystyrene microspheres improves the water permeability of the material. DETAILED DESCRIPTION
[0020] In order to facilitate the understanding of the present invention, the present invention will be described more fully below. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present invention more thorough and comprehensive.
[0021] Example 1
[0022] A tunnel slag unfired permeable brick is made of the following raw materials in parts by weight: 60 parts of tunnel slag, 20 parts of filler, 20 parts of fly ash, 40 parts of P.O52.5 ordinary Portland cement, 2 parts of calcium lignin sulfonate, 6 parts of pore-forming agent, and 15 parts of water; the particle size of the tunnel slag is 8 mm; the filler is a mixture of microsilica powder and iron tailings in a mass ratio of 2:1; the pore-forming agent is a mixture of perlite and polystyrene microspheres in a mass ratio of 1:1; the diameter of the polystyrene microspheres is 100 um.
[0023] The method for preparing the tunnel waste slag unfired permeable brick is carried out according to the following steps:
[0024] (1) According to the weight ratio, 60 parts of tunnel waste were taken and put into an 8 mm square sieve for screening. The screened tunnel waste was put into a container for cleaning and drying. 20 parts of filler, 20 parts of fly ash, 40 parts of P.O52.5 ordinary Portland cement, 2 parts of calcium lignin sulfonate, 6 parts of pore former and 15 parts of water were added. After mixing evenly, the mixture was put into a cement mortar mixer and stirred for 5 minutes to prepare a slurry.
[0025] (2) placing the stirred slurry into a mold, applying a pressure of 10 MPa and maintaining the pressure for 50 seconds, and pressing it into a green body;
[0026] (3) The green body is naturally dried and then cured; the curing temperature is 25° C., the curing humidity is greater than 95%, and the curing time is 28 days.
[0027] Example 2
[0028] A tunnel slag unfired permeable brick is made of the following raw materials in parts by weight: 40 parts of tunnel slag, 12 parts of filler, 12 parts of fly ash, 25 parts of P.O52.5 ordinary Portland cement, 1 part of sodium lignin sulfonate, 5 parts of pore-forming agent, and 12 parts of water; the particle size of the tunnel slag is 6 mm; the filler is a mixture of boron titanium magnesium stone and hydroxy boron magnesium stone in a mass ratio of 1:1; the pore-forming agent is a mixture of perlite and polystyrene microspheres in a mass ratio of 1:1; the diameter of the polystyrene microspheres is 80 um.
[0029] The method for preparing the tunnel waste slag unfired permeable brick is carried out according to the following steps:
[0030] (1) According to the weight ratio, 40 parts of tunnel waste were taken and sieved through a 6 mm square sieve. The sieved tunnel waste was placed in a container for cleaning and drying. 12 parts of filler, 12 parts of fly ash, 25 parts of P.O52.5 ordinary Portland cement, 1 part of sodium lignin sulfonate, 5 parts of pore-forming agent, and 12 parts of water were added. After mixing evenly, the mixture was placed in a cement mortar mixer and stirred for 4 minutes to prepare a slurry.
[0031] (2) placing the stirred slurry into a mold, applying a pressure of 8 MPa and maintaining the pressure for 40 seconds to press it into a green body;
[0032] (3) The green body is naturally dried and then cured; the curing temperature is 22° C., the curing humidity is greater than 95%, and the curing time is 24 days.
[0033] Example 3
[0034] A tunnel slag unfired permeable brick is made of the following raw materials in parts by weight: 75 parts of tunnel slag, 27 parts of filler, 28 parts of fly ash, 45 parts of P.O52.5 ordinary Portland cement, 3 parts of sodium lignin sulfonate, 8 parts of pore-forming agent, and 20 parts of water; the particle size of the tunnel slag is 10 mm; the filler is a mixture of boron titanium magnesium stone and hydroxy boron magnesium stone in a mass ratio of 1:1; the pore-forming agent is a mixture of perlite and polystyrene microspheres in a mass ratio of 1:1; the diameter of the polystyrene microspheres is 180 um.
[0035] The method for preparing the tunnel waste slag unfired permeable brick is carried out according to the following steps:
[0036] (1) According to the weight ratio, 75 parts of tunnel waste were taken and sieved through a 10 mm square sieve. The sieved tunnel waste was placed in a container for cleaning and drying. 27 parts of filler, 28 parts of fly ash, 45 parts of P.O52.5 ordinary Portland cement, 3 parts of sodium lignin sulfonate, 8 parts of pore-forming agent, and 20 parts of water were added. After mixing evenly, the mixture was placed in a cement mortar mixer and stirred for 6 minutes to prepare a slurry.
[0037] (2) placing the stirred slurry into a mold, applying a pressure of 15 MPa and maintaining the pressure for 70 seconds, and pressing it into a green body;
[0038] (3) The green body is naturally dried and then cured; the curing temperature is 30° C., the curing humidity is greater than 95%, and the curing time is 32 days.
[0039] Comparative Example 1
[0040] A tunnel slag unfired permeable brick is made of the following raw materials in parts by weight: 60 parts of tunnel slag, 20 parts of microsilica powder, 20 parts of fly ash, 40 parts of P.O52.5 ordinary Portland cement, 2 parts of calcium lignin sulfonate, 6 parts of pore-forming agent, and 15 parts of water; the particle size of the tunnel slag is 8 mm; the pore-forming agent is a mixture of perlite and polystyrene microspheres in a mass ratio of 1:1; the diameter of the polystyrene microspheres is 100 um.
[0041] The method for preparing the tunnel waste slag unfired permeable brick is carried out according to the following steps:
[0042] (1) According to the weight ratio, 60 parts of tunnel waste were taken and put into an 8 mm square sieve for screening. The screened tunnel waste was placed in a container for cleaning and drying. 20 parts of microsilica powder, 20 parts of fly ash, 40 parts of P.O52.5 ordinary Portland cement, 2 parts of calcium lignin sulfonate, 6 parts of pore-forming agent, and 15 parts of water were added. After mixing evenly, the mixture was placed in a cement mortar mixer and stirred for 5 minutes to prepare a slurry;
[0043] (2) placing the stirred slurry into a mold, applying a pressure of 10 MPa and maintaining the pressure for 50 seconds, and pressing it into a green body;
[0044] (3) The green body is naturally dried and then cured; the curing temperature is 25° C., the curing humidity is greater than 95%, and the curing time is 28 days.
[0045] Comparative Example 2
[0046] A tunnel slag unfired permeable brick is made of the following raw materials in parts by weight: 60 parts of tunnel slag, 20 parts of iron tailings, 20 parts of fly ash, 40 parts of P.O52.5 ordinary Portland cement, 2 parts of calcium lignin sulfonate, 6 parts of pore-forming agent, and 15 parts of water; the particle size of the tunnel slag is 8 mm; the pore-forming agent is a mixture of perlite and polystyrene microspheres in a mass ratio of 1:1; the diameter of the polystyrene microspheres is 100 um.
[0047] The method for preparing the tunnel waste slag unfired permeable brick is carried out according to the following steps:
[0048] (1) According to the weight ratio, 60 parts of tunnel waste were taken and put into an 8 mm square sieve for screening, the screened tunnel waste was put into a container for cleaning and drying, 20 parts of iron tailings, 20 parts of fly ash, 40 parts of P.O52.5 ordinary Portland cement, 2 parts of calcium lignin sulfonate, 6 parts of pore formers, and 15 parts of water were added, and the mixture was evenly mixed and then put into a cement mortar mixer for stirring for 5 minutes to prepare a slurry;
[0049] (2) placing the stirred slurry into a mold, applying a pressure of 10 MPa and maintaining the pressure for 50 seconds, and pressing it into a green body;
[0050] (3) The green body is naturally dried and then cured; the curing temperature is 25° C., the curing humidity is greater than 95%, and the curing time is 28 days.
[0051] Comparative Example 3
[0052] A tunnel slag unfired permeable brick is made of the following raw materials in parts by weight: 60 parts of tunnel slag, 20 parts of filler, 20 parts of fly ash, 40 parts of P.O52.5 ordinary Portland cement, 2 parts of calcium lignin sulfonate, 6 parts of perlite, and 15 parts of water; the particle size of the tunnel slag is 8 mm; the filler is a mixture of microsilica powder and iron tailings in a mass ratio of 2:1.
[0053] The method for preparing the tunnel waste slag unfired permeable brick is carried out according to the following steps:
[0054] (1) According to the weight ratio, 60 parts of tunnel waste were taken and put into an 8 mm square sieve for screening. The screened tunnel waste was placed in a container for cleaning and drying. 20 parts of filler, 20 parts of fly ash, 40 parts of P.O52.5 ordinary Portland cement, 2 parts of calcium lignin sulfonate, 6 parts of perlite, and 15 parts of water were added. After mixing evenly, the mixture was put into a cement mortar mixer and stirred for 5 minutes to prepare a slurry;
[0055] (2) placing the stirred slurry into a mold, applying a pressure of 10 MPa and maintaining the pressure for 50 seconds, and pressing it into a green body;
[0056] (3) The green body is naturally dried and then cured; the curing temperature is 25° C., the curing humidity is greater than 95%, and the curing time is 28 days.
[0057] Comparative Example 4
[0058] A tunnel slag unfired permeable brick is made of the following raw materials in parts by weight: 60 parts of tunnel slag, 20 parts of filler, 20 parts of fly ash, 40 parts of P.O52.5 ordinary Portland cement, 2 parts of calcium lignin sulfonate, 6 parts of polystyrene microspheres, and 15 parts of water; the particle size of the tunnel slag is 8 mm; the filler is a mixture of microsilica powder and iron tailings in a mass ratio of 2:1; the diameter of the polystyrene microspheres is 100 um.
[0059] The method for preparing the tunnel waste slag unfired permeable brick is carried out according to the following steps:
[0060] (1) According to the weight ratio, 60 parts of tunnel waste were taken and put into an 8 mm square sieve for screening, the screened tunnel waste was put into a container for cleaning and drying, 20 parts of filler, 20 parts of fly ash, 40 parts of P.O52.5 ordinary Portland cement, 2 parts of calcium lignin sulfonate, 6 parts of polystyrene microspheres, and 15 parts of water were added, and the mixture was evenly mixed and then put into a cement mortar mixer for stirring for 5 minutes to prepare a slurry;
[0061] (2) placing the stirred slurry into a mold, applying a pressure of 10 MPa and maintaining the pressure for 50 seconds, and pressing it into a green body;
[0062] (3) The green body is naturally dried and then cured; the curing temperature is 25° C., the curing humidity is greater than 95%, and the curing time is 28 days.
[0063] Comparative Example 5
[0064] A tunnel slag unfired permeable brick is made of the following raw materials in parts by weight: 75 parts of tunnel slag, 27 parts of boron titanium magnesium stone, 28 parts of fly ash, 45 parts of P.O52.5 ordinary Portland cement, 3 parts of sodium lignin sulfonate, 8 parts of pore-forming agent, and 20 parts of water; the particle size of the tunnel slag is 10 mm; the pore-forming agent is a mixture of perlite and polystyrene microspheres in a mass ratio of 1:1; the diameter of the polystyrene microspheres is 180 um.
[0065] The method for preparing the tunnel waste slag unfired permeable brick is carried out according to the following steps:
[0066] (1) According to the weight ratio, 75 parts of tunnel waste were taken and sieved through a 10 mm square sieve, the sieved tunnel waste was placed in a container for cleaning and drying, 27 parts of boron titanium magnesium stone, 28 parts of fly ash, 45 parts of P.O52.5 ordinary Portland cement, 3 parts of sodium lignin sulfonate, 8 parts of pore-forming agent, and 20 parts of water were added, and the mixture was evenly mixed and then placed in a cement mortar mixer and stirred for 6 minutes to prepare a slurry;
[0067] (2) placing the stirred slurry into a mold, applying a pressure of 15 MPa and maintaining the pressure for 70 seconds, and pressing it into a green body;
[0068] (3) The green body is naturally dried and then cured; the curing temperature is 30° C., the curing humidity is greater than 95%, and the curing time is 32 days.
[0069] Comparative Example 6
[0070] A tunnel slag unfired permeable brick is made of the following raw materials in parts by weight: 75 parts of tunnel slag, 27 parts of hydroxyboron magnesium stone, 28 parts of fly ash, 45 parts of P.O52.5 ordinary Portland cement, 3 parts of sodium lignin sulfonate, 8 parts of pore-forming agent, and 20 parts of water; the particle size of the tunnel slag is 10 mm; the pore-forming agent is a mixture of perlite and polystyrene microspheres in a mass ratio of 1:1; the diameter of the polystyrene microspheres is 180 um.
[0071] The method for preparing the tunnel waste slag unfired permeable brick is carried out according to the following steps:
[0072] (1) According to the weight ratio, 75 parts of tunnel waste were taken and sieved through a 10 mm square sieve, the sieved tunnel waste was placed in a container for cleaning and drying, 27 parts of hydroxyboric acid magnesium stone, 28 parts of fly ash, 45 parts of P.O52.5 ordinary Portland cement, 3 parts of sodium lignin sulfonate, 8 parts of pore-forming agent, and 20 parts of water were added, and the mixture was evenly mixed and then placed in a cement mortar mixer and stirred for 6 minutes to prepare a slurry;
[0073] (2) placing the stirred slurry into a mold, applying a pressure of 15 MPa and maintaining the pressure for 70 seconds, and pressing it into a green body;
[0074] (3) The green body is naturally dried and then cured; the curing temperature is 30° C., the curing humidity is greater than 95%, and the curing time is 32 days.
[0075] Experimental example:
[0076] The compressive strength of the samples was tested using a YAW-3000 microcomputer-controlled electro-hydraulic servo pressure testing machine; each material was tested 5 times. SPSS24.0 software was used for statistical analysis, and the quantitative data results were used for (mean ± standard deviation), the Kolmogorov-Smirnov test was used for data normality test, and for data that met the normal distribution, the t-test was used to compare the mean differences between the two groups, with P < 0.05 as the difference being statistically significant. The test results are shown in Table 1-2:
[0077] Table 1
[0078]
[0079] Note: * represents P < 0.05 compared with the group in Example 1.
[0080] Table 2
[0081]
[0082] Note: * represents P < 0.05 compared with the group in Example 3.
[0083] The water permeability coefficient of the samples was measured according to the standard GB / T 25993-2010 "Permeable Pavement Bricks and Permeable Road Panels", and each material was measured three times; the results are shown in Table 3:
[0084] Table 3
[0085]
[0086] Note: * represents P < 0.05 compared with the group in Example 1.
[0087] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A tunnel waste slag unfired permeable brick, characterized in that: The invention is prepared from the following raw materials in parts by weight: 30-80 parts of tunnel waste, 10-30 parts of filler, 10-30 parts of fly ash, 20-50 parts of cement, 1-3 parts of water reducing agent, 4-8 parts of pore-forming agent and 10-20 parts of water.
2. The tunnel waste slag unfired permeable brick according to claim 1 is characterized in that: The filler is one or more of microsilica powder, iron tailings, boron titanium magnesium stone, and hydroxy boron magnesium stone.
3. The tunnel waste slag unfired permeable brick according to claim 2 is characterized in that: The filler is a mixture of microsilica powder and iron tailings in a mass ratio of 2:1; or a mixture of boron titanium magnesium stone and hydroxy boron magnesium stone in a mass ratio of 1:
1.
4. The tunnel waste slag unfired permeable brick according to claim 1 is characterized in that: The cement is P.O52.5 ordinary Portland cement.
5. The tunnel waste slag unfired permeable brick according to claim 1 is characterized in that: The water reducing agent is one or more of calcium lignin sulfonate, sodium lignin sulfonate, and sodium β-naphthalenesulfonate formaldehyde condensate.
6. The tunnel waste slag unfired permeable brick according to claim 1, characterized in that: The particle size of the tunnel waste is 4-10 mm.
7. The tunnel waste slag unfired permeable brick according to claim 1, characterized in that: The pore-forming agent is a mixture of perlite and polystyrene microspheres in a mass ratio of 1:1; the diameter of the polystyrene microspheres is 30-200 um.
8. The method for preparing the tunnel waste slag unfired permeable brick according to claim 1, characterized in that: Follow these steps: (1) According to the weight ratio, 30-80 parts of tunnel waste are put into a 4-10 mm square sieve for screening, the screened tunnel waste is put into a container for cleaning and drying, 10-30 parts of filler, 10-30 parts of fly ash, 20-50 parts of cement, 1-3 parts of water reducer, 4-8 parts of pore former, and 10-20 parts of water are added, and after mixing evenly, the mixture is put into a cement mortar mixer and stirred for 3-6 minutes to prepare a slurry; (2) placing the stirred slurry into a mold, applying pressure and maintaining the pressure for 30-80 seconds to press it into a green body; (3) The green body is naturally dried and then cured.
9. The method for preparing tunnel waste slag unfired permeable bricks according to claim 8, characterized in that: The applied pressure in step (2) is 5-15 MPa.
10. The method for preparing tunnel waste slag unfired permeable bricks according to claim 8, characterized in that: The curing temperature in step (3) is 20-30° C., the curing humidity is greater than 95%, and the curing time is 20-35 days.
Citation Information
Cited By
High-content fly ash unfired water permeable brick and preparation method thereof
CN121470891A
High-content fly ash non-burning water permeable brick and preparation method thereof
CN121470891B